Monetary policy transmission channels and the performance of the real sectors in selected sub-Saharan African countries: a system-GMM approach - Ifeoma Florence Onaga; Augustine C. Arize; Josaphat U. J Onwumere; Ebere Ume Kalu (Future Business Journal)
Abstract This study investigated the impact of monetary policy channels on the real sector performance in selected sub-Saharan African countries. This study covers the period 1990 to 2020. The broad objective of the study was to examine the impact of monetary policy transmission channels on the real sectors of selected sub-Saharan African countries within the period, 1990–2020. Using the system generalized method of moments (sys-GMMs) amidst other pre-estimation and post-estimation tests, it was discovered that credit and exchange rate channels positively drove agricultural productivity, while interest rate channel exerted a negatively significant influence. Conversely, credit and exchange rate channels were found to negatively affect manufacturing, while interest rate channels had no significant impact on the manufacturing sector. Given the overwhelming impact of monetary policy channels on both the agricultural and manufacturing sectors of the SSA economies, it is recommended that effective monetary policy framework be put in place to continually create positive transmission effect on the real and productive sectors of the economy.